1967
DOI: 10.1111/j.1476-5381.1967.tb02173.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Observations on the Pressor Action of Propranolol

Abstract: Propranolol was introduced by Black, Crowther, Shanks, Smith & Dornhorst (1964) as a potent 8-adrenergic receptor blocking agent. In the previous paper (Kayaalp & Kiran, 1966), evidence was presented for the fact that the sustained pressor response elicited by this drug in the sympathetically denervated perfused hind limbs of the dog is due to the release of catecholamines from the adrenal medulla.The present work was undertaken to determine if the release of catecholamines from the adrenal medulla is the only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1975
1975
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…This observation is in accordance with that of Kayaalp and Turker [18], who have shown that in the hind limb of dogs subjected to the infusion of phentolamine, propranolol caused a sustained rise in perfusion pressure, and with that of Regoli [9], who has shown that hypertension as a result of the adminis tration of p-blockers may be potentiated in the presence of an a-blocker. We have also found that the pressor effect of a p-antagonist or rather, the antagonism of the hypotensive effect of phentolamine, showed dose-depen dency and it occurred with a pr or piselective as well as a nonselective p-blocker.…”
Section: Discussionsupporting
confidence: 80%
“…This observation is in accordance with that of Kayaalp and Turker [18], who have shown that in the hind limb of dogs subjected to the infusion of phentolamine, propranolol caused a sustained rise in perfusion pressure, and with that of Regoli [9], who has shown that hypertension as a result of the adminis tration of p-blockers may be potentiated in the presence of an a-blocker. We have also found that the pressor effect of a p-antagonist or rather, the antagonism of the hypotensive effect of phentolamine, showed dose-depen dency and it occurred with a pr or piselective as well as a nonselective p-blocker.…”
Section: Discussionsupporting
confidence: 80%
“…A paradoxical pressor response to the administration of a fiadrenoceptor antagonist has been shown to occur in rats anaesthetized with urethane (Kayaalp & Turker, 1967;Dasgupta, 1968;Yamamoto & Sekiya, 1969;Regoli, 1970;Sugawara et al, 1980;Himori et al, 1984). The pressor response in the anaesthetized rat was enhanced in the presence of an a-adrenoceptor antagonist (Yamamoto & Sekiya, 1969;Regoli, 1970;Sugawara et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The depletion of catecholarines by reserpine has been reported to develop more ,lowly and to he less complete in the adrenal medulla than in the other tissues including the heart and blood vessels (28). The vasoconstric tion caused by propranolol in anesthetized dog hind limb has been reported to be due to catecholamines released from the adrenal medulla (29,30).…”
Section: Discussionmentioning
confidence: 99%